Análisis de aprovechamiento y valoración de las colillas de cigarrillo, teniendo en cuenta el componente ambiental, social y económico - Cubides Morato, Viviana Marcela; Cárdenas Montaña, Jésica Lorena (Universidad Antonio Nariño, 2021)
The increase in environmental pollution is becoming more and more notorious, and generates changes that can be perceived with the deterioration of biodiversity, loss of ecosystems, extinction of species and even human health. For this reason, different organizations and governments have joined the task of educating the population about proper waste management, providing environmentally friendly spaces, and setting goals that help mitigate the impacts that are currently experienced, in order to ensure a future with quality of life.